Psychometric Properties of the Theory of Mind Task Battery (French Version) in Neurotypical Children and Intellectually Disabled Children - Nathalie Nader-Grosbois; Poline Simon; Emilie Jacobs; Marine Houssa (MDPI AG, 2024)
These studies tested the psychometric properties of the French version of the Theory of Mind (ToM) Task Battery (vf) in typically developing (TD) children and intellectually disabled (ID) children. The Battery was administered to 649 TD children (2 ½ to 12 years old) in Study 1 and 155 ID (4 ½ to 14 ½ years old) in Study 2. Their mothers completed questionnaires: in both studies, the Theory of Mind Inventory (ToMI-1-vf); in Study 1, the Griffith Empathy Measure (GEM-vf) and the Emotion Regulation Checklist (ERC-vf); and in Study 2, the Social Competence and Behavior Evaluation (SCBE-vf). The Battery showed good internal consistency in both groups. Positive links with age and differences between age groups were identified in their performances. Convergent validity was confirmed by positive correlations between TD children's scores in the Battery and in ToMI1-vf, in empathy, in emotion regulation, and by a negative correlation with emotion dysregulation. In ID children, their scores in the Battery were positively linked with those in ToMI-1-vf, in some scales of SCEB-vf, and had a low level of internalizing problems. This Battery presents good psychometric qualities and could be useful for explicit assessment of ToM in TD and ID children in future research and intervention.